Third Canadian Geotechnical Colloquium: Ice forces on wide structures - Kry, P. R. (Canadian Geotechnical Journal, 1980)
Successful use of artificial islands as exploration drilling platforms in the southern Beaufort Sea requires an understanding of the interactions of ice sheets with wide structures. Ice forces exerted on wide structures arise from the mechanical processes inherent in particular ice failure modes as environmental stresses move an ice sheet past a structure. Four primary ice failure modes occur against wide structures: flexure, rubble formation, buckling, and crushing. The horizontal forces associated with these modes differ by more than two orders of magnitude depending on structure geometry, ice sheet properties, and ice movement rates. Structure width influences the occurrence of ice failure modes, the ice failure stresses, and the total forces that can be exerted on a structure by an ice sheet. The relative inability to clear failed ice around wide structures (compared with narrow structures) leads to rubble formation when ice movement is continuous. After consolidation, the resulting rubble field can amplify forces exerted on the structure. Increased structure width generally results in decreased expected forces per unit width of structure. For crushing, the most serious ice failure mode for island design, increased structure width generates the possibility of nonsimultaneous failure. The resulting averaging of statistical variations across the width leads to reduced expected stresses for wide compared to narrow structures.